Second order sliding mode controller interlinked with D-STATCOM for mitigation of total harmonic distortion. (6th July 2022) - Swetha, K.; Sivachidambaranathan, V.
Power quality (PQ) is demonstrated as any power crisis that consequence in the misdirection of user devices. Electrical PQ turns out to be widely concerned with both electric appliances and customers. Voltage fluctuation remains as the most important PQ crisis as it has a major effect on both the equipment and production environment. D-STATCOM is a significant device, which enhances the power factor and sustains stable distribution voltage and alleviates harmonics in the distribution network. D-STATCOM minimises the voltage fluctuations and voltage instability of the power system that results in the speedy revival of system voltage after contingency occurrence. However, the THD problem remains a major issue in D-STATCOM devices that affects system performance. Hence, in this paper, efforts are made to minimise the THD problem in D-STATCOM devices by connecting the second order sliding mode controller (SoSMC) to D-STATCOM linked system. The main objective of the proposed controlled model is to minimise the THD so that the enhanced power quality can be attained. Moreover, the performance of the SoSMC controller is evaluated over the traditional PI controllers, and the results are analysed.